Implementasi Prinsip Green Financing dalam Pengelolaan Keuangan Masjid: Perspektif Pengurus dan Jamaah - Harahap, Mufti Fahrizal; Mufti Fahrizal Harahap (Masjiduna : Junal Ilmiah Stidki Ar-Rahmah, 2024)
This study aims to explore the implementation of green financing  principles in mosque financial management from the perspectives of mosque administrators and congregants. In a global context increasingly emphasizing the importance of environmental sustainability, mosques as centers of social and spiritual activities have significant potential to contribute to environmental preservation efforts through the adoption of green financing . This qualitative research employs in-depth interviews and focus group discussions (FGD) with mosque administrators and congregants in several mosques in Indonesia. The findings indicate that understanding of green financing  among administrators and congregants varies, but there is a growing awareness of the importance of environmentally friendly financial practices. Mosque administrators identify several key challenges in implementing green financing , including limited resources, lack of technical support, and resistance to change. On the other hand, congregants express enthusiasm for supporting environmental initiatives but require further education on the concepts and benefits of green financing . The study concludes that the successful implementation of green financing  principles in mosque financial management requires a holistic approach that includes capacity building for administrators, active participation of congregants, and collaboration with Islamic financial institutions and the government. These findings are expected to inform the development of policies and programs that support sustainable mosque financial management.